Marketing Solutions to the Challenges of a VUCA Environment: Proceedings of the 2023 GMA-GAMMA Joint Symposium, Seoul, Korea, July 20-23, 2023 - (:unkn) unknown (My University, 2024)
This book contains selected papers from the 2023 Greek Marketing Academy and the Global Alliance of Marketing and Management Associations Joint Symposium (GMA-GAMMA2023) held from July 20 to 23, 2023, in Seoul, Korea. It presents cutting-edge research in the marketing field, showcases how the recent challenges have affected marketing management and/or marketing communications and introduces the solutions to the practical problems under the Volatile, Uncertain, Complex and Ambiguous (VUCA) environment.
Keywords: Marketing Management; Marketing Communications; Digital Marketing; Digital Transformation; VUCA marketing environment; Marketing Technologies; Mediterranean, CEE, and MENA regions; GMA-GAMMA; GMA-GAMMA2023